Juridical Analysis on the Criminal Act of Online Shop Fraud in Indonesia - Karo Karo, Rizky; Sebastian, Agnes (University of Jember, 2019)
The development of technology has led to the sales and purchases of products and services online. However, the absence of a physical store prevents the prospective buyers from physically assessing the quality of the product/service. This leads to the emerging issue of online shop fraud. This paper aims to analyse the scope of online shop fraud within Indonesian laws and regulations, as well as the legal enforcement by Indonesian authorities to eradicate online shop fraud. This research uses the normative juridical method, which utilises secondary data such as books, journals and relevant legal products. This research finds that the Criminal Act of online shop fraud is regulated under Article 28 paragraph 1 of Law Number 11 Year 2008 following its amendment to Law Number 19 Year 2016 on Electronic Information and Transaction. The current efforts for legal enforcement of online shop fraud is performed in both preventive and repressive manners. Keywords: Online Shop, Fraud, Cybercrime